Monitoring students of the 1st semester of the Medicine course in an extension project focused on healthy practices in Primary Health Care (Research, Society and Development, 2022)
The routine of a healthy life is essential for the prevention of comorbidities such as diabetes and hypertension. With this, health promotion activities in the primary care environment is fundamental, since it is considered the main means of access for users to the Unified Health System. In relation to medical training, correlating the introduction of students in a primary care environment with a health education practice on healthy practices is essential as a strategy for providing knowledge both for the population and for students and professionals. The present study aims to report the experience in the development of a project in good health practices with students of the 1st semester of the Medicine course, through educational dynamics in a Basic Health Unit in Fortaleza - CE. Among the actions, a biscuit was prepared representing a blood vessel with fat molecules, engravings with different types of food, walks on the beach, in addition to the creation of folders and a profile on social networks for greater dissemination of information. The creation of this project served as an incentive for the population to seek a better quality of life and to show students, teachers and monitors the importance of an empathic conversation with patients, so that it was possible to know their challenges in achieving a healthy life. The elaboration of these activities is a great strategy for introducing students, who are starting a course in a health area, in the Primary Care environment.